NMN improves cardiac function in SIRT3 knockout mice via the SIRT1/PGC-1α pathway - Xiyao Zhao; Mengrui He; Lina He; Ruijie Han; Yanan Liu (Scientific Reports)
Abstract SIRT3 knockout mice develop cardiac insufficiency due to decreased mitochondrial function. However, upregulation of the NAD+/NADH ratio can compensate for SIRT3 deficiency through the SIRT1/PGC-1α pathway, thereby improving mitochondrial function. We therefore hypothesized that upregulation of SIRT1 expression could improve cardiac function in SIRT3 knockout mice through its interactive compensatory effect. We first determined that SIRT3 knockout mice would develop cardiac insufficiency at 8 weeks of age by ultrasound cardiac function testing, and then we selected 6-week-old SIRT3 knockout mice with similar body weights of both sexes and performed intraperitoneal injections of NMN over a 14-day period to increase the content of NAD + in the myocardial tissue of the mice. The results showed that NMN injection effectively increased the NAD + content as well as the NAD+/NADH ratio within the myocardial tissue of SIRT3 knockout mice and stimulated the expression of SIRT1 protein. In addition, protein expression of PGC-1α and its downstream molecules as well as molecules related to subunits of the respiratory chain complex was increased in mouse myocardial mitochondria. Meanwhile, NMN injection improved the cardiomyocyte and mitochondrial structure of mice, ultimately ameliorating cardiac insufficiency in SIRT3 knockout mice. In conclusion, our results suggest that NMN can compensate for SIRT3 deficiency via the SIRT1/PGC-1α pathway and improve mitochondrial biosynthesis and oxidative respiration, thereby improving cardiac function in Sirt3−/− mice. This may provide new ideas for the clinical treatment of cardiac insufficiency.